The city of Lattakia in classical Eras (A study of the information contained in archaeological inscriptions and historical texts) - غانم سليمان سمير (Latakia University Journal - Arts and Humanities Sciences Series, 2022)
Lattakia is one of the main historical cities in Syria on the eastern coast of the Mediterranean. The city has lived from the second millennium BC an intense history of various civilizations: Phoenicians, Assyrians, Persians, Greeks, Romans, Byzantines and the Arabs. During the classical eras (Hellenistic and Roman) the city played important civilized roles; In the Hellenistic era Lattakia was one of the most important Seleucid cities in Syria after its founding by Seleucus Nicator, and later during the rule of his successors, became one of the important centers of Hellenistic culture in the civilized world. In the Roman era, the cities of the Syrian coast as Lattakia became one of the most important cities of the Republic at the beginning and the Roman Empire later. Here, the influence of the city of Lattakia appeared which played a major role in the political, cultural and economic history of the Roman era. It suffices to mention the resort of the Roman consuls and emperors to Lattakia during the successive Roman conflicts to control it in the end of the republican period, and later during the imperial period in the second century AD, which confirms the city’s political and economic importance.